Limites e contribuições do uso da EME para pesquisas de cunho qualitativo na aquisição do PB - Ré, Alessandra Del [UNESP]; Hilário, Rosângela Nogarini (My University, 2014)
The main objective of this paper is to answer the following question: how can we draw a parallel, during the analysis of the data, between children who are at different moments in the language acquisition process or who belong to different populations (children that are monolingual, bilingual, with language disorders, etc.)? In order to answer this question, we are discussing the advantages and limitations of adopting a measure like MLU, from English Mean Length of Utterance, or EME as it was named in Brazil, proposed by Roger Brown (1973). We intend to verify the effective contribution of these measures to the studies in the area and propose an adaptation in the studies that use a qualitative approach. Firstly, we recall the study of the criteria proposed by Brown (1973), Scliar-Cabral (1976), Parker & Brorson (2005), Parisse & Le Normand (2006), and Araújo (2007), and by scholars of Brazilian Portuguese morphology, like Câmara Jr (2009), Monteiro (2002), and Kehdi (1990), among others. Secondly, from a dialogic-discursive point of view (BAKHTIN, 2006; BAKHTIN/ VOLOSHINOV, 1992, 1981), we provide as an example the research on the plural in the language acquisition process (HILÁRIO, 2010, 2011b, 2012). The reflections made indicate that EME may be a useful measure for the researches on language acquisition. Nevertheless, adaptations should be done and its inherent problems should be taken into account, especially if other factors are considered – like the age, the number of types/occurrences, the maximum limit of items per utterance etc. – although it is not the only parameter of analysis. Considering that EME may vary according to the conditions of production and may not reflect the qualitative changes in the children’s discourse, other factors should be analyzed, like the context of the discourse, the participants involved etc.

Este trabalho tem por objetivo responder à seguinte questão: como colocar em paralelo, no momento da análise dos dados, crianças que estão em momentos diferentes do processo de aquisição da linguagem e/ou que pertencem à populações diferentes (crianças monolíngues, bilíngues, com distúrbios de linguagem etc.)? Para responder a essa questão, discutiremos as vantagens e limitações de se adotar uma medida como o MLU, do inglês Mean Length of Utterance, ou EME como foi nomeada no Brasil, proposta por Roger Brown (1973), bem como de outras similares, verificando a efetiva contribuição das mesmas para os estudos na área e levantando uma proposta de adaptação para os estudos de natureza qualitativa.Em um primeiro momento, retomamos o estudo dos critérios propostos por Brown (1973), Scliar-Cabral (1976), Parker e Brorson (2005), Parisse e Le Normand (2006) e Araújo (2007), e de estudiosos da morfologia do PB, como Câmara Jr (2009), Monteiro (2002) e Kehdi (1990), entre outros, para, em seguida, partindo de um ponto de vista dialógico-discursivo (BAKHTIN, 2006; BAKHTIN/VOLOSHINOV, 1992, 1981), trazermos um exemplo de pesquisa que trata do plural no processo de aquisição da linguagem (HILÁRIO 2010, 2011b, 2012). As reflexões apontam para o fato de que a EME pode ser uma medida útil para as pesquisas em aquisição da linguagem, feitas as devidas adaptações e levando-se em conta todos os problemas que lhe são inerentes, especialmente se somada a outros fatores – como a idade, o número de tipos/ocorrências, o limite máximo de itens por enunciado etc. –, porém não como único parâmetro de análise. Visto que a EME pode variar de acordo com as condições de produção e não refletir as mudanças qualitativas no discurso infantil, outros fatores devem ser analisados, como o contexto discursivo, os participantes envolvidos etc.
Keywords: MLU; Qualitative researches; Language acquisition; Dialogical approach; EME; Pesquisas qualitativas; Aquisição da linguagem; Abordagem dialógica